2017
DOI: 10.4103/njcp.njcp_56_17
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of male condom utilization in Plateau State, Nigeria

Abstract: The prevalence of male condom use is low in Plateau State. The predictors of condom use are level of wealth, being unmarried, and primary level of education. Having only a primary level of education and been in the middle class reduces the likelihood of using condoms while being unmarried increases it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…This is despite the majority of the participants in the current study affirming access to condoms, with more than half (69%) indicating that they found condom use in marriage acceptable, others indicating that they could ask their partners to use condoms, and still others stating that they would not mind if the partner asked to use a condom. Similar results have been found in other studies that were conducted in Kenya, Nigeria, and South Africa [ 10 , 16 , 17 ]. Interestingly, more than half of the participants indicated that they would consider using condoms in future.…”
Section: Discussionsupporting
confidence: 91%
“…This is despite the majority of the participants in the current study affirming access to condoms, with more than half (69%) indicating that they found condom use in marriage acceptable, others indicating that they could ask their partners to use condoms, and still others stating that they would not mind if the partner asked to use a condom. Similar results have been found in other studies that were conducted in Kenya, Nigeria, and South Africa [ 10 , 16 , 17 ]. Interestingly, more than half of the participants indicated that they would consider using condoms in future.…”
Section: Discussionsupporting
confidence: 91%
“…There was significant association between both of educational and marital state of respondent with condom use; this result is in line with the findings of the studies conducted in Nigeria and Mexico City. 15,16 There was higher level of condom use 17.6% among higher socioeconomic status, this result was consistent with a study conducted in Pakistan. 17 The result may be due to a better accessibility to family planning services and an easier access to information about awareness and prevention from STIs by people from higher socio-economic class.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that 68% of undergraduates in South-eastern Nigeria are sexually active, 17.9% of these undergraduates have more than two sexual partners per year and 13.7% have more than five sexual partners per year [15]. Similar reports of high level of unprotected sexual intercourse with multiple sexual partners among University undergraduates have been reported in Southern Nigeria [11], North central Nigerian [10], Ethiopia [16] and China [17]. The factors responsible for this multiple sexual partners are satisfying sexual urge, peer pressure, ignorance, promiscuity, and sexual addiction [18].…”
Section: Introductionmentioning
confidence: 73%
“…However, a significant percentage does not consistently use condom during sexual intercourse [9]. Barriers to male condom use identified among Nigerian undergraduates are reduced pleasure during sex, partners' decision, not protective for pregnancy, difficult to use, not affordable, allergy to latex, not readily available, and religion [10] [11]. There is also a very poor knowledge and use of female condom among the Nigerian Undergraduates [12], which primarily has been attributed to unavailability and difficulty in using it [13] [14] [15].…”
Section: Introductionmentioning
confidence: 99%